Are pediatric Open Access journals promoting good publication practice? An analysis of author instructions - Wolff Robert F; Meerpohl Joerg J; Antes Gerd; von Elm Erik (BMC, 2011)
Abstract Background Several studies analyzed whether conventional journals in general medicine or specialties such as pediatrics endorse recommendations aiming to improve publication practice. Despite evidence showing benefits of these recommendations, the proportion of endorsing journals has been moderate to low and varied considerably for different recommendations. About half of pediatric journals indexed in the Journal Citation Report referred to the Uniform Requirements for Manuscripts of the International Committee of Medical Journal Editors (ICMJE) but only about a quarter recommended registration of trials. We aimed to investigate to what extent pediatric open-access (OA) journals endorse these recommendations. We hypothesized that a high proportion of these journals have adopted recommendations on good publication practice since OA electronic publishing has been associated with a number of editorial innovations aiming at improved access and transparency. Methods We identified 41 journals publishing original research in the subject category "Health Sciences, Medicine (General), Pediatrics" of the Directory of Open Access Journals http://www.doaj.org. From the journals' online author instructions we extracted information regarding endorsement of four domains of editorial policy: the Uniform Requirements for Manuscripts, trial registration, disclosure of conflicts of interest and five major reporting guidelines such as the CONSORT (Consolidated Standards of Reporting Trials) statement. Two investigators collected data independently. Results The Uniform Requirements were mentioned by 27 (66%) pediatric OA journals. Thirteen (32%) required or recommended trial registration prior to publication of a trial report. Conflict of interest policies were stated by 25 journals (61%). Advice about reporting guidelines was less frequent: CONSORT was referred to by 12 journals (29%) followed by other reporting guidelines (MOOSE, PRISMA or STARD) (8 journals, 20%) and STROBE (3 journals, 7%). The EQUATOR network, a platform of several guideline initiatives, was acknowledged by 4 journals (10%). Journals published by OA publishing houses gave more guidance than journals published by professional societies or other publishers. Conclusions Pediatric OA journals mentioned certain recommendations such as the Uniform Requirements or trial registration more frequently than conventional journals; however, endorsement is still only moderate. Further research should confirm these exploratory findings in other medical fields and should clarify what the motivations and barriers are in implementing such policies.